(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
In the text the author is anylizing the marital property regime of the spouses in the Macedonian family law. The author points that Macedonian Family Law hasn’t suffered changes for decades. This is the reason why there are many legal gaps in the provisions that regulate marital property regime. On the other side in the last decades marital and family relations have ondergone a lot of changes. Given this fact, the author is giving proposals for thoroughly regulation of the marital property relations. Crucial reform in the civil code will be introduction of the marital agreement upon which the partners will have opportunity to regulate their property relations upon their will and necessities.